The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.jallcom.2017.06.052
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of photoluminescence in intrinsically disordered CaZrO3 crystals: First principles modeling of the excited electronic states

Abstract: CaZrO3 (CZO) powders were synthesized at different temperatures (400, 600, 800, and 1000 °C) and characterized by X-ray diffraction, Raman and ultraviolet-visible spectroscopic methods, along with photoluminescence (PL) emissions. First principle calculations based on the density functional theory (DFT), using a periodic cell models, provide a theoretical framework for understanding the PL spectra based on the localization and characterization of the ground and electronic excited states.Fundamental (singlet, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
(65 reference statements)
2
11
0
Order By: Relevance
“…We link the excited states theory to the generation of electron-hole pairs, providing a deeper understanding of optical effects in the solid state. This new approach was proposed in previous studies and has been confirmed in the present work 25 . The proposed connection between excited states and optical properties is well established in quantum chemical approaches; however, the present quantum evidence of dangling bonds generating electron-trapping levels and localizing spin density is entirely new.…”
Section: Figuresupporting
confidence: 85%
See 3 more Smart Citations
“…We link the excited states theory to the generation of electron-hole pairs, providing a deeper understanding of optical effects in the solid state. This new approach was proposed in previous studies and has been confirmed in the present work 25 . The proposed connection between excited states and optical properties is well established in quantum chemical approaches; however, the present quantum evidence of dangling bonds generating electron-trapping levels and localizing spin density is entirely new.…”
Section: Figuresupporting
confidence: 85%
“…It is important to point out that in this study the Eu 3+ doping of the CZO matrix was modeled allowing lattice and atomic position relaxation for the singlet state, and calculations were carried out for both bulk and slab models, using the optimized cell for ordered and disordered models of CZO reported in our previous work 25 ; this enabled the computational treatment of the main electronic features associated with the doping process and the optical properties. well-defined peaks, denoting a high degree of crystallinity, without any secondary phases.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Wulff proposal refers to a simple relation between E surf and the distance in the normal direc tion from the center of the crystallite, which also allows this ideal morphology to be modified by tuning the surface energies of the different facets [62,63]. In recent years, this method was successfully applied for different kinds of materials, showing excellent agreement between theoretical predicted and experimental reported morphologies [45,[64][65][66][67].…”
Section: Superficial Magnetism and Crystal Morphologymentioning
confidence: 99%